Gender Issues in Islamic Family Law: Perspectives from History, Philosophy, and Sociology of law - Nurhikmah, Nurhikmah; Yumna, Hanim (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This research explores gender issues in Islamic family law from the perspective of history, philosophy and legal sociology. Islamic family law, which regulates various aspects of domestic life, often places men and women in different roles, with the view that these differences are complementary. However, in the modern context, the interpretation of Islamic law regarding gender faces challenges, especially in relation to demands for equality. This research uses a qualitative approach with literature study methods to analyze classical and contemporary sources, as well as looking at the application of Islamic family law in society. Research findings show that although Islamic family law offers basic rights for women, its implementation is often influenced by patriarchal norms that limit women's participation in family decisions. From the perspective of legal philosophy, there are differences in views between traditional interpretations that emphasize the complementarity of gender roles and modern interpretations that advocate equality. On the other hand, from a legal sociology perspective, the practice of Islamic family law in society is greatly influenced by social and cultural factors, resulting in challenges for women in demanding their rights. However, the Islamic family law reform movement continues to grow, driven by increasing awareness of the importance of gender equality in Islam. This research concludes that although challenges remain, opportunities exist to reform Islamic family law to make it more inclusive and fair for women, particularly through education, social advocacy, and the role of the state in legislation. Abstrak: Penelitian ini mengeksplorasi masalah gender dalam hukum keluarga Islam dari perspektif sejarah, filsafat, dan sosiologi hukum. Hukum keluarga Islam, yang mengatur berbagai aspek kehidupan rumah tangga, sering kali menempatkan laki-laki dan perempuan dalam peran yang berbeda, dengan pandangan bahwa perbedaan ini bersifat komplementer. Namun, dalam konteks modern, interpretasi hukum Islam terkait gender menghadapi tantangan, terutama dalam kaitannya dengan tuntutan kesetaraan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur untuk menganalisis sumber-sumber klasik dan kontemporer, serta melihat penerapan hukum keluarga Islam di masyarakat. Temuan penelitian menunjukkan bahwa meskipun hukum keluarga Islam menawarkan hak-hak dasar bagi perempuan, penerapannya sering kali dipengaruhi oleh norma-norma patriarkal yang membatasi partisipasi perempuan dalam keputusan keluarga. Dari perspektif filsafat hukum, ada perbedaan pandangan antara tafsir tradisional yang menekankan komplementaritas peran gender dan tafsir modern yang mengadvokasi kesetaraan. Di sisi lain, dari perspektif sosiologi hukum, praktik hukum keluarga Islam di masyarakat sangat dipengaruhi oleh faktor sosial dan budaya, sehingga menghasilkan tantangan bagi perempuan dalam menuntut hak-hak mereka. Namun, gerakan reformasi hukum keluarga Islam terus berkembang, didorong oleh kesadaran yang semakin meningkat tentang pentingnya kesetaraan gender dalam Islam. Penelitian ini menyimpulkan bahwa meskipun tantangan tetap ada, ada peluang untuk mereformasi hukum keluarga Islam agar lebih inklusif dan adil bagi perempuan, terutama melalui pendidikan, advokasi sosial, dan peran negara dalam legislasi.